Advanced Chemical Looping Materials for CO2 Utilization: A Review - Hu, Jiawei; Galvita, Vladimir V.; Poelman, Hilde; Marin, Guy B. (Materials, 2018)
Combining chemical looping with a traditional fuel conversion process yields a promising technology for low-CO2-emission energy production. Bridged by the cyclic transformation of a looping material (CO2 carrier or oxygen carrier), a chemical looping process is divided into two spatially or temporally separated half-cycles. Firstly, the oxygen carrier material is reduced by fuel, producing power or chemicals. Then, the material is regenerated by an oxidizer. In chemical looping combustion, a separation-ready CO2 stream is produced, which significantly improves the CO2 capture efficiency. In chemical looping reforming, CO2 can be used as an oxidizer, resulting in a novel approach for efficient CO2 utilization through reduction to CO. Recently, the novel process of catalyst-assisted chemical looping was proposed, aiming at maximized CO2 utilization via the achievement of deep reduction of the oxygen carrier in the first half-cycle. It makes use of a bifunctional looping material that combines both catalytic function for efficient fuel conversion and oxygen storage function for redox cycling. For all of these chemical looping technologies, the choice of looping materials is crucial for their industrial application. Therefore, current research is focused on the development of a suitable looping material, which is required to have high redox activity and stability, and good economic and environmental performance. In this review, a series of commonly used metal oxide-based materials are firstly compared as looping material from an industrial-application perspective. The recent advances in the enhancement of the activity and stability of looping materials are discussed. The focus then proceeds to new findings in the development of the bifunctional looping materials employed in the emerging catalyst-assisted chemical looping technology. Among these, the design of core-shell structured Ni-Fe bifunctional nanomaterials shows great potential for catalyst-assisted chemical looping.